Acute spinal cord injury is associated with mitochondrial dysfunction in mouse urothelium. Issue 6 (18th May 2019) - Kullmann, Aura F.; Truschel, Steven T.; Wolf‐Johnston, Amanda S.; McDonnell, Bronagh M.; Lynn, A. M.; Kanai, Anthony John; Kessler, Thomas M.; Apodaca, Gerard; Birder, Lori A.
Abstract: Aim: To characterize the effects of acute spinal cord injury (SCI) on mitochondrial morphology and function in bladder urothelium and to test the therapeutic efficacy of early treatment with the mitochondrially targeted antioxidant, MitoTempo. Methods: We used a mouse model of acute SCI by spinal cord transection between the T8‐T9 vertebrae with or without MitoTempo delivery at the time of injury followed by tissue processing at 3 days after SCI. Control, SCI, and SCI‐MitoTempo‐treated mice were compared in all experimental conditions. Assessments included analysis of markers of mitochondrial health including accumulation of reactive oxygen species (ROS), morphological changes in the ultrastructure of mitochondria by transmission electron microscopy, and Western blot analysis to quantify protein levels of markers for autophagy and altered mitochondrial dynamics. Results: SCI resulted in an increase in oxidative stress markers and ROS production, confirming mitochondrial dysfunction. Mitochondria from SCI mice developed large electron‐dense inclusions and these aberrant mitochondria accumulated throughout the cytoplasm suggesting an inability to clear dysfunctional mitochondria by mitophagy. SCI mice also exhibited elevated levels of dynamin‐related protein 1 (DRP1), consistent with a disruption of mitochondrial dynamics. Remarkably, treatment with MitoTempo reversed many of the SCI‐induced abnormalities that we observed. Conclusions: Acute SCI negatively and severely affects mitochondrial health of bladder urothelium. Early treatment of SCI with MitoTempo may be a viable therapeutic agent to mitigate these deleterious effects.